Mild SARS-CoV-2 Infection with the Omicron Variant Mimicking Metastatic Cancer on Whole-Body 18-F FDG PET/CT Imaging - Gunnhild Helmsdal; Sissal Clemmensen; Jann Mortensen; Marnar Fríðheim Kristiansen; Maria Skaalum Petersen; Herborg L. Johannesen (COVID)
We present a case with unusual findings on nuclear imaging after mild SARS-CoV-2 infection. During evaluation for an incidentaloma, 18F-Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography imaging showed activity in the thyroid gland, in the lower thoracic spinal column, in portal lymph nodes, and in the terminal ileum and surrounding lymph nodes, all suspicious for metastatic cancer. The patient underwent extensive invasive and non-invasive diagnostic procedures, including biopsies of all the suspicious foci, only showing a small low-grade thyroid cancer that would often be followed and not immediately operated on. Three months later, the findings had either disappeared or were considered reactive. The patient later recalled having had mild COVID-19 seven days prior to the PET/CT.